IN SILICO STUDY OF ANTI-TYPE II DIABETES ACTIVITY OF XANTHONES WITH MOLECULAR DOCKING AND MOLECULAR DYNAMICS APPROACH - Yosephine, Michaella
Type 2 diabetes mellitus (DM) is a disease caused by insulin resistance. This disease causes hyperglycemic conditions (high blood sugar levels) that may lead to organ failure. Many types of type 2 DM medication exist, such as oral medication. Oral medication can be divided into six classes: biguanide, sulphonylurea, glinide, thiazolidinedione, dipeptidyl peptidase IV inhibitor and alpha glucosidase inhibitor. Although many types of oral medications have been discovered, the effectiveness and efficacy varies between patients, which means that there is still a need for an alternative to the existing treatments in the market. One compound group that has gained a lot of scientific interest in its antidiabetic potential is xanthones as inhibitors of two complex carbohydrate metabolizing enzymes, alphaglucosydase and alpha-amylase. The inhibition of these enzymes decrease the degradation of carbohydrates into glucose, resulting in the inhibition of the increase of blood glucose concentration. In this research, 515 three-dimensional and SMILES structures of xanthones are either collected from Pubchem (if available) or created using Avogadro. Ligands are typed with CHARMM forcefield and MMFF94 partial charge prior to docking to alpha-glucosidase (PDB Code: 2QMJ) and alpha-amylase (PDB Code: 1XD0) using PyRx. The SMILES structures are used to estimate the toxicity (oral rat LD50) and predict the physicochemical features of each xanthone. Xanthones with binding affinities higher of equal to the top tenth percentile of xanthones and oral rat LD50 values of over 500 mg/kg will have their interactions with their respective protein targets examined. In total, there are thirty-one (31) unique ligands that fulfill the cut-off values. Out of the 31 xanthones, ten are glycosylated xanthones, two are xanthonologinoids, and nine are prenylated xanthones. All 31 ligands and the standard ligand are predicted to inhibit the protein’s active site. As a result, all ligands have at least one interaction with the active site residues and residues that interact with the standard ligand. The residues found to interact with all the ligands aer Asp542 and Phe575 for protein target 2QMJ and His201 and Glu233 for protein target 1XD0. Three xanthones are chosen as the best inhibitors based on the amount of interactions with the active site residues and residues that interact with the standard ligand. The three best inhibitors for 2QMJ are L140 (3,4,5,8-Tetrahydroxy-1,2-diisoprenylxanthone), L449 (Polygalaxanthone V), and L451 (Polygalaxanthone VII), while the three best inhibitors for 1XD0 are L115 (1-O-primeverosyl-3,8-dihydroxy-5- methoxyxanthone), L316 (Garcimangosone C), and L393 (Mangostinone). All three ligands of 2QMJ were found to interact with 100% of the protein’s active site residues, while all three ligands of 1XD0 had the most interactions with the active sites and standard ligand interaction sites, as well as interact with the three catalytic sites of protein 1XD0. All six ligands and the standard ligands were able to advance to the molecular dynamics simulation. The simulation is performed using GROMACS for 2 ns, with the CHARMM force field and TIP3P water model. Before performing the production stage, system equilibration was performed at a constant temperature and pressure of 310 K and 1 atm using the NVT and NPT ensemb and energy minimization was performed using the steepest descent algorithm. From the graphs of potential energy, temperature, and density of the system, it was found that equilibration and minimization were successfully performed on all eight systems. From the results of the production stage, all systems were found to fluctuate in terms of interaction energy, number of interactions, and the types of interactions formed. The standard ligand always had the strongest interaction energy, while prenylated xanthones always had the weakest interaction energy. However, prenylated xanthones showed better ability in keeping most of their initial interactions constant from the beginning, middle, to the end of the simulation compared to the standard ligand and glycosylated xanthones.